Fine structure of the spermatozoon in three species of Cambaridae (Arthropoda: Crustacea: Decapoda) Cambarus robustus, Orconectes propinquus and Orconectes rusticus: a comparative biometrical study - Yazicioglu, Buket (PeerJ, 2016)
The ultrastructure of spermatozoa in three species of cambarid crayfish, Cambarus robustus, Orconectes propinquus, and Orconectes rusticus, were studied and compared with eight previously studied species from different crayfish families using morphological features and biometrical data. The ultrastructure of spermatozoa show a generally conserved pattern including an acrosome and nucleus in the anterior and posterior parts of the cell, respectively, radial arms that wrap around the nucleus, and the whole cell is enclosed by an extracellular capsule. The most outstanding morphological feature in spermatozoa of three studied cambarid crayfish is the crest-like protrusions in the anterior part of the acrosome that can be used as one of the features for distinguishing the members of this family. Results of biometrical data reveal that acrosome size in the representatives of Parastacidae are the smallest, while representatives of Astacidae show the biggest acrosome. The acrosome size in species belonging to Cambaridae occupy an intermediate position between the two other families of freshwater crayfish. In conclusion, a combination of morphological features and biometrical data of spermatozoa can help distinguishing different species of the freshwater crayfish.